2022
DOI: 10.55711/cdnl9128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Migration on Transformation to Sustainability: Poverty and Development in Bangladesh

Abstract: This book contains the findings from the third wave of a migration focused panel survey in Bangladesh. It examines the interrelationships between labour migration, poverty, and development based on 6,100 interviews including international labour migrants, internal migrants and non-migrant households spanning 20 districts of Bangladesh. The first wave of survey (2014) found that among these three groups poverty level is much lower for international labour migrant households. The second wave (2017), demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Relatives or friends overseas often assist men in migrating, while others rely on migration agencies, reflecting social ties (IOM 2010;Siddiqui and Mahmood 2015). Their co-ethnic communities also facilitate migrant men's access to jobs and economic prospects in the host country (Pfeffer and Parra 2009).…”
Section: Transnational Migration Socio-spatial Locations and Masculin...mentioning
confidence: 99%
“…Relatives or friends overseas often assist men in migrating, while others rely on migration agencies, reflecting social ties (IOM 2010;Siddiqui and Mahmood 2015). Their co-ethnic communities also facilitate migrant men's access to jobs and economic prospects in the host country (Pfeffer and Parra 2009).…”
Section: Transnational Migration Socio-spatial Locations and Masculin...mentioning
confidence: 99%
“…Whereas, the actual figure for the year 2006 was USD 679 million only, contributing 1.6% of the GDP of that time (IOM, 2014). On the academic side, Adams and Page (2005), Kalim and Shahbaz (2009), Anyanwu and Erhijakpor (2010), Gupta et al, (2009), Siddiqui et al, (2012), Azam et al, (2016) are among many researchers found remittance positively impacting the poverty and economic growth in different countries.…”
Section: Shahzad Anwar Faizan Ahmad Wajid Kabirmentioning
confidence: 99%
“…Many scholars agreed on the positive, often economic, effects of internal migration on poverty reduction at individual and household levels outside China. Siddiqui [3] summarised that migration offers migrants subsistence, job opportunities and financial income increases. Sugiyarto, Deshingkar, and McKay [4] found in Indonesia that there was a significant fall in the poverty rate among total internal migrants, where the rate of return migrants experienced a greater decline than that of current migrants, implying that it takes time for migrants to escape from poverty.…”
Section: Literature Reviewmentioning
confidence: 99%